Predictive Accuracy of Heart Failure-Specific Risk Equations in an Electronic Health Record-Based Cohort. (November 2020) - Bavishi, Aakash; Bruce, Matthew; Ning, Hongyan; Freaney, Priya M.; Glynn, Peter; Ahmad, Faraz S.; Yancy, Clyde W.; Shah, Sanjiv J.; Allen, Norrina B.; Vupputuri, Suma X.; Rasmussen-Torvik, Laura J.; Lloyd-Jones, Donald M.; et al.
Abstract : Background: Guidelines recommend identification of individuals at risk for heart failure (HF). However, implementation of risk-based prevention strategies requires validation of HF-specific risk scores in diverse, real-world cohorts. Therefore, our objective was to assess the predictive accuracy of the Pooled Cohort Equations to Prevent HF within a primary prevention cohort derived from the electronic health record. Methods: We retrospectively identified patients between the ages of 30 to 79 years in a multi-center integrated healthcare system, free of cardiovascular disease, with available data on HF risk factors, and at least 5 years of follow-up. We applied the Pooled Cohort Equations to Prevent HF tool to calculate sex and race-specific 5-year HF risk estimates. Incident HF was defined by the International Classification of Diseases codes. We assessed model discrimination and calibration, comparing predicted and observed rates for incident HF. Results: Among 31 256 eligible adults, mean age was 51.4 years, 57% were women and 11% Black. Incident HF occurred in 568 patients (1.8%) over 5-year follow-up. The modified Pooled Cohort Equations to Prevent HF model for 5-year risk prediction of HF had excellent discrimination in White men (C-statistic 0.82 [95% CI, 0.79–0.86]) and women (0.82 [0.78–0.87]) and adequate discrimination in Black men (0.69 [0.60–0.78]) and women (0.69 [0.52–0.76]). Calibration was fair in all race-sex subgroups (χ 2 <20). Conclusions: A novel sex- and race-specific risk score predicts incident HF in a real-world, electronic health record-based cohort. Integration of HF risk into the electronic health record may allow for risk-based discussion, enhanced surveillance, and targeted preventive interventions to reduce the public health burden of HF. Abstract : Supplemental Digital Content is available in the text.